Melitensia: Estudio visual de espacios de creación malteses y narrativas de sus propietarios - Alonso Sanz, Mª Amparo (Communiars. Revista de Imagen, Artes y Educación Crítica y Social, 2024)
Globalisation and gentrification are endangering the cultural and aesthetic values of the Mediterranean countries, especially in the most touristic cities. The importance of the aesthetics of the everyday is the basis for an observation of this gradual transformation and the creation of memory archives. For this investigation Malta was chosen as a place of special interest because of its small size and location. The aim is to gather a ‘melitensia’ view of the life stories of adults who, after retirement, have maintained a creative activity that is aesthetically projected in their working environments. The methodology combines Qualitative Research and Arts-Based Research, using drift as a method of data collection, through instruments such as open interviews and photography. The results offer testimonies and sample series of 20 people who give an account of the evolution of Malta over the last 50 years. They highlight the aesthetic values associated with their own identity and corporeality, faith, family heritage, interest in the material, spatial organisation and the construction of visualities. It is concluded that ‘melitensia’ authenticity, in aesthetic terms, is in imminent danger of extinction. Although the active performance of creative, artistic and manufactured tasks by older people still sustains a shared identity, retains a common visual culture and roots the traditional in a changing world.